Acclimatation of the roe deer (Capreolus capreolus L.) introduced in a supramediterranean habitat and its occupation of space - Maillard, D; Gaudin, J C; Reudet, D; Boutin, J M (REVUE D ECOLOGIE-LA TERRE ET LA VIE, 1999)
In 1988 and 1989, we captured 74 roe deer (Capreolus capreolus) in the Chize National Reserve in France and transferred them to the Monts de Vaucluse. Thirteen individuals were followed by radio-tracking during two years. The study area, a supramediterranean habitat dominated by Quercus humilis and Quercus ilex covered 40,000 ha. The instrumented deer were located daily during the three first months, the longest time required to settle on a home range, and once a week thereafter. These data allowed us to calculate survival rates and size of home ranges. The mean survival rate during the first year after the introduction was 85 %. Except for one adult male and one adult female, all radio-equipped deer established their home range within 3 km of the release site. The time required for definitive establishment on a home range varied from 45 to 85 days after release. The mean area prospected before settling on a home range was greater for adults (n = 5) than for juveniles (n = 6) (2,240 ha vs. 478 ha). Conversely, the mean home range size after the period of prospection was greater for juveniles (n = 6) than for adults (n = 4) (823 ha vs. 342 ha). If capture, transport and release are carried out under good conditions, the roe deer can adapt to the Mediterranean climate and habitat.
APS
Keywords: Chize National Reserve; Quercus humilis; Quercus ilex; roe deer

Cynegetical development of the French Mediterranean ``matorral'' scrublands: Case of wild ungulates - Maillard, D; Melac, O; Gaudin, J C; Vassant, J (GIBIER FANE SAUVAGE - GAME AND WILDLIFE, VOL 15 (SPECIAL NUMBER PTS 2 AND 3) 1998, 1998)
Since the beginning of the seventies, the marorrals (garrigues, maquis, and holly oak, Quercus ilex, copses) are slowly being colonized by roe deer, Capreolus capreolus, white wild boar; Sus scrofa, populations are stongly increasing. This phenomenon is mainly due to a relative low hunting pressure compared to the potential huntable population, to the disappearance of traditional farming practices (rural abandonment) causing the matorrals to extend, to the compensations paid to farmers since 1969, and to an increase in food resources (ageing of holly oak copses). As for red deer, Cervus elaphus, its population is increasing very slowly: The uncontrolled increase in wild boar populations is causing intolerable damages to farmers, especially in high-quality crops (arboriculture, vines, market-garden crops), which have been expanding since the productive lands in the bottom of the valley are being cultivated and agricultural techniques have improved. In the years to come, the ungulates frequenting the garrigue may become a harvestable resource if the two main sympatric species (wild boar and roe deer) which are occupying areas of some 30,000 ha, are wisely managed and the following parameters are taken into account : - amount of food produced in the habitats (annual mast crops); - damage control by controlled hunting in each massif, and damage prevention (protection or dissuation); - appropriate management of ungulate territories and the effective control of their populations based on hunting bag analyses in the middle and at the end of the hunting season. Most of ail it is important that before applying the ``population/environment/damage{''} model in each massif or management unit, clear management objectives be defined in agreement with the farmers.
IUGB XXIIIrd Congress, LYON, FRANCE, SEP 01-06, 1997
Keywords: roe deer; Sus scrofa; Wild boar; wild ungulate

Roe deer habitat selection in Spain: constraints on the distribution of a species - Virgos, E.; Tellería, J. L. (Canadian Journal of Zoology, 1998)
This study analyzes the role of summer habitat selection in determining the distribution of a population of roe deer (Capreolus capreolus L.) in central Spain, where surplus individuals have emigrated from mountains to the surrounding plateaus during the last decade. The species was more abundant in the mesic mountain forests (Scots pine (Pinus sylvestris), Pyrenean oak (Quercus pyrenaica)) than in the xeric, sclerophyllous holm oak (Quercus ilex) forests of surrounding plateaus. Roe deer prefer patches occupied by brambles (Rubus spp.) and rose bushes (Rosa spp.) and patches with higher cover on pastures and moors (Erica spp. and Calluna spp.). These vegetation types are linked to moist soils in the Mediterranean zone, indicating that roe deer prefer the moister, more productive patches. Roe deer actively selected productive patches covered by leguminous shrubs (Sarothamnus, Retama) and rejected poor patches covered by Cistus ladanifer and Cistus laurifolius (two shrubs that produce chemicals toxic to other plants). Low summer primary productivity of xeric, sclerophyllous forests can explain the low abundance of roe deer in these forests. This supports the view that habitat constraints limit numbers and distribution of this Palaearctic species at the southern edge of its range.
doi: 10.1139/z98-065doi: 10.1139/z98-065The following values have no corresponding Zotero field: publisher: NRC Research Press
Keywords: habitat selection; leguminous shrubs (PG); roe deer

Roe deer habitat selection in Spain: constraints on the distribution of a species - Virgos, E; Tellería, J L (Canadian Journal of Zoology, 1998)
This study analyzes the role of summer habitat selection in determining the distribution of a population of roe deer (Capreolus capreolus L.) in central Spain, where surplus individuals have emigrated from mountains to the surrounding plateaus during the last decade. The species was more abundant in the mesic mountain forests (Scots pine (Pinus sylvestris), Pyrenean oak (Quercus pyrenaica)) than in the xeric, sclerophyllous holm oak (Quercus ilex) forests of surrounding plateaus. Roe deer prefer patches occupied by brambles (Rubus spp.) and rose bushes (Rosa spp.) and patches with higher cover on pastures and moors (Erica spp. and Calluna spp.). These vegetation types are linked to moist soils in the Mediterranean zone, indicating that roe deer prefer the moister, more productive patches. Roe deer actively selected productive patches covered by leguminous shrubs (Sarothamnus, Retama) and rejected poor patches covered by Cistus ladanifer and Cistus laurifolius (two shrubs that produce chemicals toxic to other plants). Low summer primary productivity of xeric, sclerophyllous forests can explain the low abundance of roe deer in these forests. This supports the view that habitat constraints limit numbers and distribution of this Palaearctic species at the southern edge of its range.
doi: 10.1139/z98-065
Keywords: habitat selection; leguminous shrubs (PG); roe deer

Distribution of an increasing roe deer population in a fragmented Mediterranean landscape - Tellería, José Luis; Virgós, Emilio (Ecography, 1997)
This paper describes roe deer Capreolus capreolus distribution in central Spain, where the species has spread from the mountains into peripheral agricultural areas In this region, it is more abundant in forest fragments near the mountains than in those further away, in pine and oak woodlands than in sclerophyllous forests, and in forests with open water than in those lacking this resource The paper also analyzes whether habitat quality and geographic location of forests with respect to roe deer source areas are the two basic causes of its distribution, as predicted by some models of the species distribution in fragmented landscapes The results corroborate this hypothesis revealing that roe deer abundance is linked negatively to sclerophyllous forest cover and distance from mountains We conclude that this type of farmland seems to be sub-optimal for roe deer in comparison with forested, moist mountains
The following values have no corresponding Zotero field: publisher: Blackwell Publishing Ltd
Keywords: abundance; Distribution patterns; forest cover; habitat quality (voyant); roe deer

Distribution of an increasing roe deer population in a fragmented Mediterranean landscape - Tellería, José Luis; Virgós, Emilio (Ecography, 1997)
This paper describes roe deer Capreolus capreolus distribution in central Spain, where the species has spread from the mountains into peripheral agricultural areas In this region, it is more abundant in forest fragments near the mountains than in those further away, in pine and oak woodlands than in sclerophyllous forests, and in forests with open water than in those lacking this resource The paper also analyzes whether habitat quality and geographic location of forests with respect to roe deer source areas are the two basic causes of its distribution, as predicted by some models of the species distribution in fragmented landscapes The results corroborate this hypothesis revealing that roe deer abundance is linked negatively to sclerophyllous forest cover and distance from mountains We conclude that this type of farmland seems to be sub-optimal for roe deer in comparison with forested, moist mountains
Keywords: abundance; Distribution patterns; forest cover; habitat quality (voyant); roe deer